Automation comes to analog. - Martin, B.
In this paper, the author describes how the long overshadowed by the digital world, the black-magic realm of analog design is gaining the spotlight and acquiring software tools of its own
Keywords: CAD; Analog chip design; Hardware description languages; Software tools